Exploring Tertiary ESL learners’ Affective Attributes Toward Online Reading - Kangxing Dong; Chiam Kee Swan; Hafizoah Kassim (Premise: Journal of English Education and Applied Linguistics, 2021)
The Covid-19 pandemic has significantly accelerated digitization of higher education worldwide and reading online has become vital for students to grasping new knowledge and understanding course contents. As educators, it is important to understand our students’ affective attributes towards the new normal of reading online. Within this scope, the study aims to develop a self-report instrument on affective attributes towards online reading among tertiary ESL learners, and to examine the specific affective attributes students display towards online reading. The Survey of Online Reading Affective Attributes was adapted and developed to measure tertiary ESL learners’ affective attributes towards online reading for academic and study-related purposes. This questionnaire was administered to 130 tertiary ESL learners. Principal components analysis was performed and the results confirmed the three affective factors were self-efficacy, motivation, and anxiety. In addition, the analysis of the survey data revealed that the majority of students, in general, were relatively self-efficacious, motivated, and less anxious towards online reading. However, it was discovered that nearly one-third of students were relatively anxious towards online reading and one-fifth of them were less self-efficacious. The limitations of this study and pedagogical recommendations are further discussed in this paper.